Reorientation: Leo Strauss in the 1930s - Yaffe, Martin D.; Ruderman, Richard S.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The first comprehensive effort to examine Strauss's astonishingly wide-ranging writings of the 1930s (some of which have only recently been made available to English-speaking readers, including several herein) with a view to their unifying theme of recovering classical political philosophy.
Keywords: Science; Science, general